Lithium manganese iron phosphate positive electrode material and preparation method thereof and application in solid-state battery

By using carbon coating and graphene collaborative modification technology in lithium manganese iron phosphate positive electrode material, the problems of agglomeration, uneven coating and interface barrier effects of materials in the battery are solved, efficient dispersion and improved conductivity of the material are achieved, and the electrochemical performance and stability of the battery are significantly improved.

CN119430123BActive Publication Date: 2025-04-22ZHUZHOU SHENGHUA TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510039719.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-22
Estimated Expiration
2045-01-10

AI Technical Summary

Technical Problem

The existing lithium manganese iron phosphate positive electrode materials have particle agglomeration, uneven coating and interface hindering effects in batteries, affecting their electrochemical performance and stability.

Method used

The coordinated modification method of carbon coating and graphene is used to graft graphene oxide through polyethylene glycol and link a chain transfer agent, and then N-isopropyl acrylamide is polymerized thereon to form amphiphilic graphene, which improves its dispersion and conductivity, thereby regulating particle size and morphology and improving electrochemical properties.

Benefits of technology

It effectively inhibits particle agglomeration, improves the dispersion and conductivity of the material, enhances the battery's magnification and cycling performance, and improves the stability of the electrode material.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a lithium iron manganese phosphate positive electrode material and a preparation method thereof and an application in a solid-state battery, and relates to the technical field of lithium iron manganese phosphate positive electrode materials. The present application adopts polyethylene glycol to graft graphene oxide and links a chain transfer agent 2-methyl-2-[(dodecylthiothiocarbonyl)thio] propionic acid thereon, and then polymerizes N-isopropylacrylamide thereon by azobisisobutyronitrile, and N-isopropylacrylamide contains both a hydrophobic group isopropyl and a hydrophilic group amide group, thereby converting graphene oxide into amphiphilicity; the hydrophilic group or lipophilic group thereon is oriented in a solution to reduce the interfacial energy of the material, thereby increasing the dispersibility of the material, and plays an important role in regulating the size and morphology of the particles, on the one hand, due to the adsorption of its side chain on its surface during the growth of the crystal nucleus, the crystal nucleus orientation can be induced; on the other hand, the space formed by the layer-by-layer assembly between the graphenes makes the crystal nucleus grow inside the assembly space.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium iron manganese phosphate positive electrode materials, in particular to lithium iron manganese phosphate positive electrode materials and a preparation method thereof and application in solid-state batteries. Background Art

[0002] In today's era of rapid technological development, the demand for high-performance energy storage equipment is increasing. As a mainstream energy storage device, lithium-ion batteries require a significant improvement in the performance of their electrode materials. Lithium iron manganese phosphate materials stand out among many positive electrode materials due to their own advantages, but they also need to be modified and optimized due to some shortcomings.

[0003] In order to improve the performance of lithium manganese iron phosphate materials, there are currently main modification methods such as surface coating, ion doping and particle size control. Among them, carbon coating in surface coating has attracted much attention. Carbon coating operation is relatively easy to implement and low cost, which is a very favorable condition for large-scale production applications. From the perspective of material properties, after carbon coating, the active material has a low carbon content and will not cause too much interference to the main performance. It also has good chemical stability. Whether it is during normal battery charging and discharging or facing a complex use environment, it can effectively resist the damage to the material structure by external factors and ensure the stability of battery performance.

[0004] The functional role of carbon coating is more critical. It can inhibit particle agglomeration, maintain the dispersed state of particles, and avoid problems such as reduction of active sites and obstruction of ion diffusion due to agglomeration. At the same time, it can act as a protective layer to prevent the surface of the material from being corroded by hydrofluoric acid, because in the electrolyte system of lithium-ion batteries, hydrofluoric acid easily corrodes the surface of the positive electrode material, and the carbon coating can well isolate this corrosion. In addition, the void structure on the surface of the carbon layer is conducive to electrolyte penetration, which can promote ion transport inside the battery and improve charge and discharge performance. However, it is difficult to accurately control the quality of carbon coating. If the coating is discontinuous and uneven, some particle surfaces will not be completely coated, or the local coating layer will be too thick, resulting in the inability to fully utilize the active material. It will also affect electron transport due to the interface barrier effect, limiting the overall performance improvement of the battery.

[0005] Therefore, the present application adopts carbon coating and graphene synergistic modification to address this shortcoming, and processes the graphene to improve its dispersibility, thereby controlling the particle size and the uniform distribution between particles. Summary of the invention

[0006] The purpose of the present invention is to provide a lithium iron manganese phosphate positive electrode material and a preparation method thereof and an application in a solid-state battery, so as to solve the problems existing in the prior art.

[0007] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0008] A method for preparing a lithium manganese iron phosphate positive electrode material comprises the following preparation steps:

[0009] S1. Weigh lithium hydroxide monohydrate and phosphoric acid in a mass ratio of 1:0.75-0.85, add lithium hydroxide monohydrate and phosphoric acid to ethylene glycol with a mass of 35-40 times that of lithium hydroxide monohydrate, stir to dissolve, add amphiphilic graphene emulsion with a mass of 1-1.2 times that of ethylene glycol, stir evenly, and prepare precursor A for standby use;

[0010] S2. Weigh ferrous sulfate heptahydrate, manganese sulfate monohydrate and L-ascorbic acid in a mass ratio of 1:0.012-0.014:0.035-0.04. Under argon protection, add ferrous sulfate heptahydrate, manganese sulfate monohydrate and L-ascorbic acid to ethylene glycol with a mass of 10-12 times that of ferrous sulfate heptahydrate, stir and dissolve, and prepare precursor B for later use.

[0011] S3. Under argon protection, the precursor solution B is added dropwise to the precursor A while stirring, and after stirring for 15 to 20 minutes, the solution is transferred to a high-pressure reactor, and the reaction is carried out at a temperature of 190 to 210° C. for 22 to 24 hours. After the reaction is completed, the solution is cooled to room temperature, the lower precipitate is taken out, and the solution is washed 3 to 5 times by alternately filtering with deionized water and anhydrous ethanol. After washing, the solution is dried at a temperature of 45 to 50° C. to obtain a lithium manganese iron phosphate material;

[0012] S4. Weigh the lithium iron manganese phosphate material and the carbon source according to a mass ratio of 10:1-1.2, mix the lithium iron manganese phosphate material and the carbon source evenly, dry them completely at a temperature of 45-50°C, and perform a two-step calcination treatment on the dried material in a tubular furnace under argon protection to obtain a lithium iron manganese phosphate positive electrode material;

[0013] The amphiphilic graphene emulsion is prepared by mixing amphiphilic graphene and ethylene glycol, wherein the amphiphilic graphene is prepared by pre-oxidizing graphene, grafting polyethylene glycol and linking the chain transfer agent 2-methyl-2-[(dodecylthiocarbonyl)thio]propionic acid, and then polymerizing N-isopropylacrylamide and transferring the chain to the polyethylene glycol to prepare the amphiphilic graphene.

[0014] As an optimization, the amphiphilic graphene emulsion includes the following preparation steps: adding the amphiphilic graphene to ethylene glycol with a mass of 900 to 950 times that of the amphiphilic graphene, stirring evenly and then ultrasonically dispersing for 30 to 40 minutes for use.

[0015] As an optimization, the amphiphilic graphene includes the following preparation steps: weighing N-isopropylacrylamide monomer, modified graphene and azobisisobutyronitrile in a mass ratio of 1:0.75~0.8:0.018~0.02, adding N-isopropylacrylamide monomer, modified graphene and azobisisobutyronitrile to tetrahydrofuran with a mass of 18~20 times that of N-isopropylacrylamide monomer under nitrogen protection, stirring evenly, ultrasonically dispersing for 10~15 minutes, placing at a temperature of 65~70°C, reacting for 12~14 hours, adding 25~30 times the mass of N-isopropylacrylamide monomer after the reaction, filtering the precipitate after standing and settling, and vacuum drying to obtain amphiphilic graphene.

[0016] As an optimization, the modified graphene includes the following preparation steps: graphene oxide, polyethylene glycol, 4-dimethylaminopyridine and dicyclohexylcarbodiimide are weighed in a mass ratio of 1:2.8~3:0.8~1:1.8~2, and under nitrogen protection, the graphene oxide is added to toluene with a mass of 500~550 times that of the graphene oxide, and ultrasonically dispersed for 30~35 minutes, and then polyethylene glycol, 4-dimethylaminopyridine and dicyclohexylcarbodiimide are added, and ultrasonically dispersed for 30~35 minutes. After the ultrasonic dispersion is completed, the temperature is raised to 70~75°C, and the reaction is stirred for 22~24 hours. Stirring After stirring, the temperature was lowered to -5~0°C, 0.1~0.2 times the mass of polyethylene glycol of 2-methyl-2-[(dodecylthiothiocarbonyl)thio]propionic acid was added, and stirred for 30~35 minutes. Then, 0.6~0.7 times the mass of polyethylene glycol of dicyclohexylcarbodiimide was added again, and the mixture was reacted at -5~0°C for 30~35 minutes. Then, the mixture was transferred to 25~30°C and reacted for 22~24 hours. After the reaction was completed, the mixture was filtered and the filtered product was washed 2~3 times with toluene and deionized water respectively, and then vacuum dried at 60~65°C to obtain modified graphene.

[0017] As an optimization, the graphene oxide includes the following preparation steps: weighing flake graphite and sodium nitrate according to a mass ratio of 1:0.5-0.6, adding flake graphite and sodium nitrate to 98% concentrated sulfuric acid with a mass fraction of 40-45 times the mass of flake graphite, ultrasonicating for 30-35 minutes at a temperature of -5-0°C, adding potassium permanganate with a mass fraction of 2.8-3 times the mass of flake graphite after ultrasonication, stirring for 2-2.5 hours at a temperature of 0-5°C, and then ultrasonicating for 30-35 minutes at a temperature of 30-35°C, and then adding 95% of the mass of flake graphite. ~100 times of deionized water, then stirred for 30~35min at a temperature of 90~95℃, then added deionized water 55~60 times of the mass of the flake graphite, after standing for 20~30min, added hydrogen peroxide 30~32 times of the mass of the flake graphite with a mass fraction of 30~35%, after standing for 15~20min, added hydrochloric acid solution 45~50 times of the mass of the flake graphite with a mass fraction of 10~15%, after standing for stratification, took out the lower precipitate, washed with deionized water 3~5 times, centrifuged and washed the precipitate until neutral, to obtain graphene oxide.

[0018] As an optimization, the two-step calcination treatment in step S4 includes the following preparation steps: first calcining at a temperature of 330-350° C. for 2-2.2 h, and then calcining at a temperature of 690-700° C. for 4-4.2 h.

[0019] As an optimization, the heating and cooling rates during the two-step calcination treatment are both 5°C / min.

[0020] As an optimization, sucrose is used as the carbon source.

[0021] A lithium manganese iron phosphate positive electrode material is prepared by any of the preparation methods described above.

[0022] An application of the lithium iron manganese phosphate positive electrode material as described above in a solid-state battery.

[0023] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0024] The present application adopts polyethylene glycol to graft graphene oxide and links the chain transfer agent 2-methyl-2-[(dodecylthiothiocarbonyl)thio]propionic acid thereon, and then polymerizes N-isopropylacrylamide thereon through azobisisobutyronitrile, and N-isopropylacrylamide contains both a hydrophobic group isopropyl and a hydrophilic group amide group, so that the graphene oxide is converted into amphiphilic; the hydrophilic group or lipophilic group thereon is oriented in the solution to reduce the interfacial energy of the material, thereby increasing the dispersibility of the material, and plays an important role in regulating the size and morphology of the particles. On the one hand, during the growth of the crystal nucleus, its side chain is adsorbed on its surface, which can induce the orientation of the crystal nucleus; on the other hand, through the space formed by the layer-by-layer assembly of the graphene, the crystal nucleus is located inside the assembly space for growth, and the polymer chain segments between the layers effectively limit the direction of its growth, so that the size and morphology of the particles can be effectively regulated. In addition, the polymer chain segments between the graphene layers also effectively prevent the stacking of the graphene layers, thereby effectively increasing the overall utilization space;

[0025] Later, carbon coating was also introduced. Traditional carbon coating will result in discontinuous and uneven carbon coating, which will lead to the inability to fully utilize the active materials, and in the electrochemical reaction process, it will produce an electron transport interface barrier effect. The added graphene can effectively alleviate this situation, because graphene itself is a conductive additive and material structure design base material. Lithium manganese iron phosphate can grow on the graphene substrate, thereby improving its electrochemical properties by constructing an effective conductive network through graphene, improving the conductivity of the electrode material, and making it exhibit better rate and cycle performance. DETAILED DESCRIPTION

[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0027] Example 1

[0028] S1. Weigh flake graphite and sodium nitrate in a mass ratio of 1:0.5, add flake graphite and sodium nitrate to 98% concentrated sulfuric acid with a mass fraction of 40 times the mass of flake graphite, ultrasonicate for 30 minutes at a temperature of -5°C, add potassium permanganate with a mass fraction of 2.8 times the mass of flake graphite after ultrasonication, then stir for 2 hours at a temperature of 0°C, then ultrasonicate for 30 minutes at a temperature of 30°C, then add deionized water with a mass fraction of 95 times the mass of flake graphite, then stir for 30 minutes at a temperature of 90°C, then add deionized water with a mass fraction of 55 times the mass of flake graphite, let it stand for 20 minutes, then add 30% hydrogen peroxide with a mass fraction of 30 times the mass of flake graphite, let it stand for 15 minutes, then add 10% hydrochloric acid solution with a mass fraction of 45 times the mass of flake graphite, let it stand for stratification, take the lower precipitate, wash it with deionized water 3 times, centrifuge and wash it to neutrality to obtain graphene oxide;

[0029] S2. Weigh graphene oxide, polyethylene glycol, 4-dimethylaminopyridine and dicyclohexylcarbodiimide in a mass ratio of 1:2.8:0.8:1.8. Under nitrogen protection, add graphene oxide to toluene with a mass 500 times that of graphene oxide, and ultrasonically disperse for 30 minutes. Then add polyethylene glycol, 4-dimethylaminopyridine and dicyclohexylcarbodiimide, and ultrasonically disperse for 30 minutes. After ultrasonic dispersion, heat to 70°C, stir and react for 22 hours, and cool down after stirring. to -5°C, add 0.1 times the mass of polyethylene glycol of 2-methyl-2-[(dodecylthiothiocarbonyl)thio]propionic acid, stir for 30 minutes, add 0.6 times the mass of polyethylene glycol of dicyclohexylcarbodiimide again, react for 30 minutes at -5°C, then transfer to 25°C and react for 22 hours. After the reaction is completed, filter and wash the filtered product twice with toluene and deionized water respectively, and then dry in vacuum at 60°C to obtain modified graphene;

[0030] S3, weighing N-isopropylacrylamide monomer, modified graphene and azobisisobutyronitrile in a mass ratio of 1:0.75:0.018, adding N-isopropylacrylamide monomer, modified graphene and azobisisobutyronitrile to tetrahydrofuran (18 times the mass of N-isopropylacrylamide monomer) under nitrogen protection, stirring evenly, ultrasonically dispersing for 10 minutes, placing at a temperature of 65°C, reacting for 12 hours, adding 25 times the mass of N-isopropylacrylamide monomer after the reaction, filtering the precipitate after standing and settling, and vacuum drying to obtain amphiphilic graphene;

[0031] S4. Weigh lithium hydroxide monohydrate and phosphoric acid in a mass ratio of 1:0.75, add lithium hydroxide monohydrate and phosphoric acid to ethylene glycol with a mass of 35 times that of lithium hydroxide monohydrate, stir to dissolve, add amphiphilic graphene emulsion with a mass of 1 times that of ethylene glycol, stir evenly, and prepare precursor A for standby use; add amphiphilic graphene to ethylene glycol with a mass of 900 times that of amphiphilic graphene, stir evenly, and then ultrasonically disperse for 30 minutes for standby use;

[0032] S5. Weigh ferrous sulfate heptahydrate, manganese sulfate monohydrate and L-ascorbic acid in a mass ratio of 1:0.012:0.035. Under argon protection, add ferrous sulfate heptahydrate, manganese sulfate monohydrate and L-ascorbic acid to ethylene glycol with a mass of 10 times that of ferrous sulfate heptahydrate, stir and dissolve, and prepare precursor B for later use.

[0033] S6. Under argon protection, the precursor solution B was added dropwise to the precursor A while stirring. After stirring for 15 minutes, the mixture was transferred to a high-pressure reactor and reacted for 22 hours at 190° C. After the reaction was completed, the mixture was cooled to room temperature, the lower precipitate was taken out, and washed with deionized water and anhydrous ethanol by suction for 3 times. After washing, the mixture was dried at 45° C. to obtain lithium manganese iron phosphate material.

[0034] S7. Weigh the lithium manganese iron phosphate material and the carbon source in a mass ratio of 10:1, mix the lithium manganese iron phosphate material and the carbon source evenly, dry them completely at 45°C, and perform two-step calcination treatment on the dried material in a tube furnace under argon protection to obtain the lithium manganese iron phosphate positive electrode material; first calcination at 330°C for 2h, and then calcination at 690°C for 4h; the heating and cooling rates during the two-step calcination treatment are both 5°C / min; sucrose is used as the carbon source. .

[0035] Example 2

[0036] S1. Weigh flake graphite and sodium nitrate in a mass ratio of 1:0.55, add flake graphite and sodium nitrate to 98% concentrated sulfuric acid with a mass fraction of 42.5 times the mass of flake graphite, and ultrasonicate for 32.5 minutes at a temperature of -2.5°C. After the ultrasonication, add potassium permanganate with a mass fraction of 2.9 times the mass of flake graphite, then stir for 2.25 hours at a temperature of 2.5°C, and then ultrasonicate for 32.5 minutes at a temperature of 32.5°C, and then add deionized water with a mass fraction of 97.5 times the mass of flake graphite. water, then stirred for 32.5 minutes at a temperature of 92.5°C, and then added deionized water 57.5 times the mass of the flake graphite, and after standing for 25 minutes, added hydrogen peroxide 31 times the mass of the flake graphite with a mass fraction of 32.5%, and after standing for 17.5 minutes, added hydrochloric acid solution 47.5 times the mass of the flake graphite with a mass fraction of 12.5%, and after standing for stratification, took out the lower precipitate, and washed it with deionized water 4 times, and then centrifuged to take the precipitate and washed it to neutrality to obtain graphene oxide;

[0037] S2. Weigh graphene oxide, polyethylene glycol, 4-dimethylaminopyridine and dicyclohexylcarbodiimide in a mass ratio of 1:2.9:0.9:1.9. Under nitrogen protection, add graphene oxide to toluene (525 times the mass of graphene oxide), ultrasonically disperse for 32.5 min, then add polyethylene glycol, 4-dimethylaminopyridine and dicyclohexylcarbodiimide, ultrasonically disperse for 32.5 min. After ultrasonic dispersion, heat to 72.5 °C, stir and react for 23 h, and cool to -2.5 °C after stirring. ℃, add 2-methyl-2-[(dodecylthiothiocarbonyl)thio]propionic acid (0.15 times the mass of polyethylene glycol), stir for 32.5 minutes, add dicyclohexylcarbodiimide (0.65 times the mass of polyethylene glycol) again, and react for 32.5 minutes at -2.5℃, then transfer to 27.5℃ and react for 23 hours. After the reaction is completed, filter and wash the filtered product with toluene and deionized water for 2.5 times respectively, and then dry in vacuum at 62.5℃ to obtain modified graphene;

[0038] S3, weighing N-isopropylacrylamide monomer, modified graphene and azobisisobutyronitrile in a mass ratio of 1:0.775:0.019, adding N-isopropylacrylamide monomer, modified graphene and azobisisobutyronitrile to tetrahydrofuran (19 times the mass of N-isopropylacrylamide monomer) under nitrogen protection, stirring evenly, ultrasonically dispersing for 12.5 minutes, placing at a temperature of 67.5°C, reacting for 13 hours, adding 27.5 times the mass of N-isopropylacrylamide monomer of glacial ether after the reaction, letting it stand and precipitate, filtering the precipitate, and vacuum drying to obtain amphiphilic graphene;

[0039] S4. Weigh lithium hydroxide monohydrate and phosphoric acid in a mass ratio of 1:0.8, add lithium hydroxide monohydrate and phosphoric acid to ethylene glycol with a mass of 37.5 times that of lithium hydroxide monohydrate, stir to dissolve, add amphiphilic graphene emulsion with a mass of 1.1 times that of ethylene glycol, stir evenly, and prepare precursor A for standby use; add amphiphilic graphene to ethylene glycol with a mass of 925 times that of amphiphilic graphene, stir evenly, and then ultrasonically disperse for 35 minutes for standby use;

[0040] S5. Weigh ferrous sulfate heptahydrate, manganese sulfate monohydrate and L-ascorbic acid in a mass ratio of 1:0.013:0.0375. Under argon protection, add ferrous sulfate heptahydrate, manganese sulfate monohydrate and L-ascorbic acid to ethylene glycol with a mass 11 times that of ferrous sulfate heptahydrate, stir and dissolve, and prepare precursor B for later use.

[0041] S6. Under argon protection, the precursor solution B was added dropwise to the precursor A while stirring. After stirring for 17.5 minutes, the mixture was transferred to a high-pressure reactor and reacted for 23 hours at 200°C. After the reaction was completed, the mixture was cooled to room temperature, the lower precipitate was taken out, and washed with deionized water and anhydrous ethanol by filtration for 4 times. After washing, the mixture was dried at 47.5°C to obtain lithium iron manganese phosphate material.

[0042] S7. Weigh the lithium iron manganese phosphate material and the carbon source in a mass ratio of 10:1.1, mix the lithium iron manganese phosphate material and the carbon source evenly, dry them completely at 47.5°C, and carry out a two-step calcination treatment on the dried material in a tubular furnace under argon protection to obtain the lithium iron manganese phosphate positive electrode material; first, calcine at 340°C for 2.1h, and then calcine at 695°C for 4.1h; the heating and cooling rates during the two-step calcination treatment are both 5°C / min; sucrose is used as the carbon source.

[0043] Example 3

[0044] S1. Weigh flake graphite and sodium nitrate in a mass ratio of 1:0.6, add flake graphite and sodium nitrate to 98% concentrated sulfuric acid with a mass fraction of 45 times the mass of flake graphite, perform ultrasonic treatment for 35 minutes at a temperature of 0°C, add potassium permanganate with a mass fraction of 3 times the mass of flake graphite after ultrasonic treatment, stir for 2.5 hours at a temperature of 5°C, perform ultrasonic treatment for 35 minutes at a temperature of 35°C, add deionized water with a mass fraction of 100 times the mass of flake graphite, stir for 35 minutes at a temperature of 95°C, add deionized water with a mass fraction of 60 times the mass of flake graphite, let stand for 30 minutes, add 35% hydrogen peroxide with a mass fraction of 32 times the mass of flake graphite, let stand for 20 minutes, add 15% hydrochloric acid solution with a mass fraction of 50 times the mass of flake graphite, take the lower precipitate after standing for stratification, wash it with deionized water 5 times, centrifuge and wash the precipitate to neutrality to obtain graphene oxide;

[0045] S2. Weigh graphene oxide, polyethylene glycol, 4-dimethylaminopyridine and dicyclohexylcarbodiimide in a mass ratio of 1:3:1:2. Under nitrogen protection, add graphene oxide to toluene with a mass 550 times that of graphene oxide, and ultrasonically disperse for 35 minutes. Then add polyethylene glycol, 4-dimethylaminopyridine and dicyclohexylcarbodiimide, and ultrasonically disperse for 35 minutes. After ultrasonic dispersion, heat to 75°C, stir and react for 24 hours, and cool to 0°C after stirring. ℃, add 2-methyl-2-[(dodecylthiothiocarbonyl)thio]propionic acid (0.2 times the mass of polyethylene glycol), stir for 35 minutes, add dicyclohexylcarbodiimide (0.7 times the mass of polyethylene glycol) again, and react for 35 minutes at 0℃, then transfer to 30℃ and react for 24 hours. After the reaction is completed, filter and wash the filtered product with toluene and deionized water for 3 times respectively, and then dry in vacuum at 65℃ to obtain modified graphene;

[0046] S3, weighing N-isopropylacrylamide monomer, modified graphene and azobisisobutyronitrile in a mass ratio of 1:0.8:0.02, adding N-isopropylacrylamide monomer, modified graphene and azobisisobutyronitrile to tetrahydrofuran (20 times the mass of N-isopropylacrylamide monomer) under nitrogen protection, stirring evenly, ultrasonically dispersing for 15 minutes, placing at a temperature of 70°C, reacting for 14 hours, adding 30 times the mass of N-isopropylacrylamide monomer after the reaction, filtering the precipitate after standing and settling, and vacuum drying to obtain amphiphilic graphene;

[0047] S4. Weigh lithium hydroxide monohydrate and phosphoric acid in a mass ratio of 1:0.85, add lithium hydroxide monohydrate and phosphoric acid to ethylene glycol with a mass of 40 times that of lithium hydroxide monohydrate, stir to dissolve, add amphiphilic graphene emulsion with a mass of 1.2 times that of ethylene glycol, stir evenly, and prepare precursor A for standby use; add amphiphilic graphene to ethylene glycol with a mass of 950 times that of amphiphilic graphene, stir evenly, and then ultrasonically disperse for 40 minutes for standby use;

[0048] S5. Weigh ferrous sulfate heptahydrate, manganese sulfate monohydrate and L-ascorbic acid in a mass ratio of 1:0.014:0.04. Under argon protection, add ferrous sulfate heptahydrate, manganese sulfate monohydrate and L-ascorbic acid to ethylene glycol with a mass 12 times that of ferrous sulfate heptahydrate, stir and dissolve, and prepare precursor B for later use.

[0049] S6. Under argon protection, the precursor solution B was added dropwise to the precursor A while stirring. After stirring for 20 minutes, the mixture was transferred to a high-pressure reactor and reacted for 24 hours at a temperature of 210° C. After the reaction was completed, the mixture was cooled to room temperature, the lower precipitate was taken out, and washed with deionized water and anhydrous ethanol alternately for 5 times. After washing, the mixture was dried at a temperature of 50° C. to obtain a lithium manganese iron phosphate material;

[0050] S7. Weigh the lithium iron manganese phosphate material and the carbon source in a mass ratio of 10:1.2, mix the lithium iron manganese phosphate material and the carbon source evenly, dry them completely at 50°C, and carry out a two-step calcination treatment on the dried material in a tubular furnace under argon protection to obtain the lithium iron manganese phosphate positive electrode material; first, calcine at 350°C for 2.2h, and then calcine at 700°C for 4.2h; the heating and cooling rates during the two-step calcination treatment are both 5°C / min; sucrose is used as the carbon source.

[0051] Example 4

[0052] The only difference from Example 2 is step S4: lithium hydroxide monohydrate and phosphoric acid are weighed in a mass ratio of 1:0.8, and the lithium hydroxide monohydrate and phosphoric acid are added to ethylene glycol with a mass of 37.5 times that of the lithium hydroxide monohydrate, and after stirring to dissolve, a modified graphene emulsion with a mass of 1.1 times that of the ethylene glycol is added, and stirred evenly to prepare a precursor A for standby use; the modified graphene is added to ethylene glycol with a mass of 925 times that of the modified graphene, stirred evenly, and then ultrasonically dispersed for 35 minutes for standby use;

[0053] Example 5

[0054] The only difference from Example 2 is step S4: lithium hydroxide monohydrate and phosphoric acid are weighed in a mass ratio of 1:0.8, and the lithium hydroxide monohydrate and phosphoric acid are added to ethylene glycol with a mass of 37.5 times that of the lithium hydroxide monohydrate, and after stirring to dissolve, a graphene oxide emulsion with a mass of 1.1 times that of the ethylene glycol is added, and stirred evenly to prepare a precursor A for standby use; graphene oxide is added to ethylene glycol with a mass of 925 times that of the graphene oxide, stirred evenly, and then ultrasonically dispersed for 35 minutes for standby use;

[0055] Example 6

[0056] The only difference from Example 2 is step S4: lithium hydroxide monohydrate and phosphoric acid are weighed in a mass ratio of 1:0.8, and the lithium hydroxide monohydrate and phosphoric acid are added to ethylene glycol with a mass of 37.5 times that of the lithium hydroxide monohydrate, and stirred to dissolve, thereby preparing a precursor A for standby use;

[0057] Button battery assembly

[0058] The lithium manganese iron phosphate positive electrode material, conductive carbon black, and PVDF are dispersed in NMP solvent at a mass ratio of 8:1:1 for 6 to 8 hours to form a uniform slurry, which is coated on aluminum by a doctor blade method and vacuum dried at 80°C for 10 hours. The dried pole piece is rolled and sliced ​​to form a small round pole piece with a diameter of 12mm. The active material surface density is 1.0 - 2.0mg / cm², and then vacuum dried at 80°C for more than 12 hours. A metal lithium sheet with a diameter of 14mm is used as the counter electrode and reference electrode, the electrolyte is 1mol / L LiPF6 / EC+DMC+DEC (the volume ratio of the three is 1:1:1), and the diaphragm is selected as Celgard2500 model. The button battery is assembled in a vacuum glove box with a water and oxygen content of less than 0.1ppm.

[0059] Electrochemical performance test

[0060] The battery prepared in the above embodiment was tested for charge and discharge performance, constant current at room temperature, and rate performance test voltage range of 2.5V~4.5V. The charge and discharge rate was 0.1C for 3 cycles, 0.2C, 0.5C, 1.0C, 2.0C, 5.0C, 10.0C for 5 cycles each, and finally 0.1C for 5 cycles. The specific test results are shown in Table 1 below;

[0061] Table 1

[0062] category 0.1C / (mAh / g) 0.2C / (mAh / g) 0.5C / (mAh / g) 1.0C / (mAh / g) 2.0C / (mAh / g) 5.0C / (mAh / g) 10.0C / (mAh / g) Example 1 156.53 154.48 151.58 147.01 144.22 136.15 128.56 Example 2 156.02 152.31 149.45 145.52 140.98 133.98 124.78 Example 3 155.54 151.89 149.64 146.68 142.72 134.79 126.79 Example 4 145.65 143.85 142.72 138.30 131.95 119.26 102.25 Example 5 145.02 143.52 142.06 140.75 137.12 122.06 107.27 Example 6 146.08 143.99 141.64 137.52 131.74 121.58 110.06

[0063] The battery prepared in the above embodiment was subjected to a cycle stability test, and was cycled 100 times at 5.0C and 10.0C at room temperature, and the capacity retention rate was calculated. The specific test results are shown in Table 2 below;

[0064] Table 2

[0065] category Battery capacity retention rate after 100 cycles at 5.0C / % Battery capacity retention rate after 100 cycles at 10.0C / % Example 1 96.82 96.00 Example 2 96.34 96.60 Example 3 96.34 96.67 Example 4 91.17 89.60 Example 5 87.01 85.85 Example 6 86.50 83.26

[0066] From the comparison of the experimental data of Examples 1 to 3 in Table 1, it can be found that the lithium manganese iron phosphate positive electrode material prepared by the present invention has good electrochemical properties and still maintains good performance after multiple uses;

[0067] In Example 4, the main reason for the decline in electrochemical performance is that although the dispersibility of the grafted polyethylene glycol is improved to a certain extent compared with the original, it lacks side chains to induce crystal nucleus growth, resulting in a partial gap in the final particle morphology, which leads to a decline in overall performance, but the decline is not large, and the degree of performance decline is also low after multiple cycles;

[0068] In Example 5, the reason for the large decrease may be that the stacking of graphenes results in a smaller application space for the final material, which leads to uncontrollable overall morphology and decreased overall performance.

[0069] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A method for preparing a lithium manganese iron phosphate positive electrode material, characterized in that: The method comprises the following preparation steps: S1. Weigh lithium hydroxide monohydrate and phosphoric acid in a mass ratio of 1:0.75-0.85, add lithium hydroxide monohydrate and phosphoric acid to ethylene glycol with a mass of 35-40 times that of lithium hydroxide monohydrate, stir to dissolve, add amphiphilic graphene emulsion with a mass of 1-1.2 times that of ethylene glycol, stir evenly, and prepare precursor A for standby use; S2. Weigh ferrous sulfate heptahydrate, manganese sulfate monohydrate and L-ascorbic acid in a mass ratio of 1:0.012-0.014:0.035-0.

04. Under argon protection, add ferrous sulfate heptahydrate, manganese sulfate monohydrate and L-ascorbic acid to ethylene glycol with a mass of 10-12 times that of ferrous sulfate heptahydrate, stir and dissolve, and prepare precursor B for later use. S3. Under argon protection, the precursor solution B is added dropwise to the precursor A while stirring, and after stirring for 15 to 20 minutes, the solution is transferred to a high-pressure reactor, and the reaction is carried out at a temperature of 190 to 210° C. for 22 to 24 hours. After the reaction is completed, the solution is cooled to room temperature, the lower precipitate is taken out, and the solution is washed 3 to 5 times by alternately filtering with deionized water and anhydrous ethanol. After washing, the solution is dried at a temperature of 45 to 50° C. to obtain a lithium manganese iron phosphate material; S4. Weigh the lithium iron manganese phosphate material and the carbon source according to a mass ratio of 10:1-1.2, mix the lithium iron manganese phosphate material and the carbon source evenly, dry them completely at a temperature of 45-50°C, and perform a two-step calcination treatment on the dried material in a tubular furnace under argon protection to obtain a lithium iron manganese phosphate positive electrode material; The amphiphilic graphene emulsion is prepared by mixing amphiphilic graphene and ethylene glycol, wherein the amphiphilic graphene is prepared by pre-oxidizing graphene, grafting polyethylene glycol and linking the chain transfer agent 2-methyl-2-[(dodecylthiocarbonyl)thio]propionic acid, and then polymerizing N-isopropylacrylamide and transferring the chain to the polyethylene glycol to prepare the amphiphilic graphene.

2. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The amphiphilic graphene emulsion comprises the following preparation steps: adding the amphiphilic graphene into ethylene glycol with a mass of 900 to 950 times that of the amphiphilic graphene, stirring evenly and then ultrasonically dispersing for 30 to 40 minutes for standby use.

3. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 2, characterized in that: The amphiphilic graphene comprises the following preparation steps: weighing N-isopropylacrylamide monomer, modified graphene and azobisisobutyronitrile in a mass ratio of 1:0.75-0.8:0.018-0.02, adding the N-isopropylacrylamide monomer, modified graphene and azobisisobutyronitrile to tetrahydrofuran with a mass of 18-20 times that of the N-isopropylacrylamide monomer under nitrogen protection, stirring evenly, ultrasonically dispersing for 10-15 minutes, placing at a temperature of 65-70°C, reacting for 12-14 hours, adding icy ether with a mass of 25-30 times that of the N-isopropylacrylamide monomer after the reaction is completed, filtering the precipitate after standing and settling, and vacuum drying to obtain the amphiphilic graphene.

4. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 3, characterized in that: The modified graphene comprises the following preparation steps: weighing graphene oxide, polyethylene glycol, 4-dimethylaminopyridine and dicyclohexylcarbodiimide according to a mass ratio of 1:2.8-3:0.8-1:1.8-2, adding graphene oxide to toluene with a mass of 500-550 times that of graphene oxide under nitrogen protection, ultrasonically dispersing for 30-35 minutes, then adding polyethylene glycol, 4-dimethylaminopyridine and dicyclohexylcarbodiimide, ultrasonically dispersing for 30-35 minutes, heating to 70-75°C after ultrasonic dispersion, stirring for reaction for 22-24 hours, and ending stirring. The mixture was cooled to -5~0°C, 2-methyl-2-[(dodecylthiothiocarbonyl)thio]propionic acid (0.1~0.2 times the mass of polyethylene glycol) was added, and stirred for 30~35 minutes. Dicyclohexylcarbodiimide (0.6~0.7 times the mass of polyethylene glycol) was added again, and the mixture was reacted at -5~0°C for 30~35 minutes. The mixture was then transferred to 25~30°C and reacted for 22~24 hours. After the reaction was completed, the mixture was filtered and the filtered product was washed 2~3 times with toluene and deionized water respectively, and then dried in vacuo at 60~65°C to obtain modified graphene.

5. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 4, characterized in that: The graphene oxide comprises the following preparation steps: weighing flake graphite and sodium nitrate in a mass ratio of 1:0.5-0.6, adding the flake graphite and sodium nitrate into 98% concentrated sulfuric acid with a mass fraction of 40-45 times the mass of the flake graphite, ultrasonicating for 30-35 minutes at a temperature of -5-0°C, adding potassium permanganate with a mass fraction of 2.8-3 times the mass of the flake graphite after the ultrasonication, stirring for 2-2.5 hours at a temperature of 0-5°C, ultrasonicating for 30-35 minutes at a temperature of 30-35°C, and then adding 95-10% of the mass of the flake graphite. 0 times of deionized water, then stirred for 30-35 minutes at a temperature of 90-95°C, then added 55-60 times of deionized water as the mass of the flake graphite, allowed to stand for 20-30 minutes, then added 30-32 times of the mass of the flake graphite with a mass fraction of 30-35% hydrogen peroxide, allowed to stand for 15-20 minutes, then added 45-50 times of the mass of the flake graphite with a mass fraction of 10-15% hydrochloric acid solution, allowed to stand for stratification, removed the lower precipitate, washed with deionized water for 3-5 times, centrifuged and washed the precipitate until neutral, to obtain graphene oxide.

6. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The two-step calcination treatment in step S4 includes the following preparation steps: first, calcining at a temperature of 330-350° C. for 2-2.2 hours, and then calcining at a temperature of 690-700° C. for 4-4.2 hours.

7. The method for preparing lithium iron manganese phosphate positive electrode material according to claim 6, characterized in that: The heating and cooling rates during the two-step calcination treatment were both 5°C / min.

8. The method for preparing lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The carbon source is sucrose.

9. A lithium manganese iron phosphate positive electrode material, characterized in that: The compound is prepared by the preparation method described in any one of claims 1 to 7.

10. Use of the lithium iron manganese phosphate positive electrode material as claimed in claim 9 in a solid-state battery.

Citation Information

Patent Citations

  • Hydrophilic polythiophene grafted oxidized graphene supercapacitor electrode material and preparation method thereof

    CN109326455A

  • Graphene modified-carbon coated lithium iron phosphate material, preparation method thereof and solid-state lithium ion battery

    CN114497556A